2019
DOI: 10.2147/idr.s224518
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rapid Diagnosis Of Multidrug-Resistant Tuberculosis Impacts Expenditures Prior To Appropriate Treatment: A Performance And Diagnostic Cost Analysis</p>

Abstract: BackgroundIn this study, we aimed to describe the impact of the Genotype® MTBDRplus line probe assay (LPA) for multidrug-resistant tuberculosis (MDR-TB) on total costs in a high-burden setting in China. The second objective was to evaluate the performance of HAIN on smear-positive sputum and clinical isolates.MethodsAll definitive TB inpatients at the Shandong Provincial Chest Hospital between May 2012 and May 2017 were included in the study. Two sputum specimens were collected from each patient to conduct sme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Despite the increased costs of laboratory testing, the use of the LPAs decreases the total health care costs for Chinese patients with MDR-TB. 23 More importantly, patients are not exposed to ineffective empirical therapy, which prevents disease progression and improves clinical outcomes for patients with MDR-TB. However, extremely few patients with MDR-TB were resistant to only RIF and INH resistance in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increased costs of laboratory testing, the use of the LPAs decreases the total health care costs for Chinese patients with MDR-TB. 23 More importantly, patients are not exposed to ineffective empirical therapy, which prevents disease progression and improves clinical outcomes for patients with MDR-TB. However, extremely few patients with MDR-TB were resistant to only RIF and INH resistance in our study.…”
Section: Discussionmentioning
confidence: 99%
“…DR-TB care delays gradually improved to 28 days (IQR: 16–40) through the 3-year DR-TB care decentralization program, which included streamlining LPA testing in the clinical practice (years 2009–2011). Moreover, studies from settings with more established healthcare infrastructure (e.g., China and South Korea) also found that operational challenges diminished the potential benefit of rapid molecular testing in improving DR-TB care delays [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, reduction of these delays were not solely due the implementation of the technology alone. In an earlier phases of LPA implementation in South Africa, use of LPA for DR-TB care were much restricted and centralized at higher levels of the health and laboratory system, and caused treatment initiation delays of more than Moreover, studies from settings with more established healthcare infrastructure (e.g., China and South Korea) also found that operational challenges diminished the potential benefit of rapid molecular testing in improving DR-TB care delays [41][42][43].…”
Section: Principal Findingsmentioning
confidence: 99%
“…In a study conducted in a tertiary hospital in China, the costs were lower in the diagnosis of MDR-TB using GenoType ® owing to the reduction of the TAT for result release, but the authors did not include the costs of the multiple components 9 . In another study conducted in Russia 10 , the use of GenoType ® in routine DR-TB investigations, compared with the use of MGIT 960, was associated with a lower cost and greater success in the treatment of DR-TB.…”
Section: Cost Analysis Was Performed At the State Laboratory Of Publicmentioning
confidence: 99%
“…The accuracy and cost of conventional and molecular methods for the diagnosis of MDR-TB have been described in several countries [8][9][10] , including Brazil [11][12][13] . However, data on the costs incurred with the use of molecular tests in Public Health Laboratories are scarce, and the information obtained can be used to optimize resource management health services in countries with a unified health system, such as Brazil, particularly with the recent incorporation of GenoType ® MTBDRplus and GenoType ® MTBDRsl 14 .…”
mentioning
confidence: 99%